Vegetal fiber paper matrix impregnated with silica gel for benzene removal. (17th September 2019) - Wu, Xuannan; Ge, Tianshu; Dai, Yanjun; Wang, Ruzhu
Abstract: Removing benzene from indoor space plays an important role in indoor air purification. A novel filter with vegetal fiber paper (VFP) as matrix hosting silica gel is proposed in this paper for benzene removal. In order to investigate the feasibility and performance of this idea, firstly, three pieces of VFP samples impregnated with different amounts of silica gel are fabricated and their benzene adsorption quantities are tested. The results show that three times is recommended as the optimal number for impregnating. The VFP sample impregnated with silica gel after the third impregnating exhibits commendable coating stability and good benzene adsorption performance. Additionally, at low relative pressure ( P b / P s  ≤ 0.05), the experimental data of benzene adsorption isotherms fit well with the Langmuir model with R 2 greater than 0.97. Then, two actual filters made of VFP impregnated with silica gel after the third impregnating were fabricated. It is found that the pressure drop of the actual filter is only 1200 Pa/m when the air velocity is 2 m/s. Besides, the one‐pass efficiency of the filter can reach to 19.44%. It is expected that the silica gel coated on the filter can be modified to improve the purification performance of the filter.